TEAM GAME TOURNAMENT (TGT) COOPERATIVE MODEL EFFECT TO SENIOH HIGH SCHOOL STUDENT’S MOTIVATION - Ayu Wulandari; Relsas Yogica; Ganda Hijrah Selaras; Ristiono Ristiono (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This research is an experimental research which aims to see the influence of Teams Game Tournament (TGT) learning model on the motivation of students on immune system material at SMA Pembangunan Laboratorium UNP academic year 2018/2019. The implementation of this study does not allow researchers to control variables as a whole so that this study belongs to the quasi-experimental category with the design of control group posttest only design. Sampling in this study used saturation sampling technique. The technique of data analysis used statistical tests, namely the t test. The results of statistical tests showed that in a significant term (α = 0.05) the value of tcount> t tableis obtained, which is 3.28 > 1.67, then H0 is rejected and H1 is accepted. It can be concluded that the motivation of students using the Teams Game Tournament (TGT) learning model is higher than the motivation of students who use conventional learning. It can be interpreted that there is an influence of the Teams Game Tournament (TGT) learning model on the motivation of students on immune system material at SMA Pembangunan Laboratorium UNP.